Sobre la configuración lingüística del mensaje periodístico - Hernando Cuadrado, Luis Alberto (Estudios sobre el Mensaje Periodístico, 2002)
In this article, after emphasizing the importance of the Journalism on today’s society and describing the process of communication, a characterization of the peculiar style of the journalistic message is offered trough the analysis of the use of the lexical and grammatical most outstanding forms and structures on it, and several sections are dedicated to the syntax of the titles and the use of elements of the colloquial register.